(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Comparison of systemic inflammatory markers NLR, CRP, and interleukin-6 between patients with acute ischemic stroke and controls, and evaluation of the value of these inflammatory biomarkers in assessing stroke severity according to the NIHSS score. Subjects and Methods: Cross-sectional study with control group was conducted, including 113 patients with cerebral infarction and 113 control subjects. Inflammatory markers assessed comprised neutrophil count, lymphocyte count, neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), and interleukin-6 (IL-6). Disease severity was evaluated using NIHSS score. Results: The mean age was 65.03 ± 10.75 years, with 25.7% of patients having NIHSS ≥15. NLR was higher in the patient group compared to controls (4.11 vs 2.31; p<0.001). Similarly, CRP and IL-6 levels were elevated in the patient group (7.01 vs 3.01 mg/L and 11.94 vs 4.37 pg/mL, respectively; p<0.001). NLR showed a moderate correlation with NIHSS (r=0.599, p<0.001). CRP was positively correlated with NIHSS (r=0.429, p<0.001), while IL-6 demonstrated the strongest correlation (r=0.617, p<0.001). For identifying severe cerebral infarction, NLR had an AUC of 0.823 at a cut-off of 5.66; CRP had an AUC of 0.683 at a cut-off of 9.00 mg/L; and IL-6 had an AUC of 0.712 at a cut-off of 12.06 pg/mL. Conclusion: Systemic inflammatory biomarkers IL-6 and NLR show potential utility in supporting assessment of severity in patients with cerebral infarction.